2020
DOI: 10.1101/2020.09.28.20201475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large scale sequencing of SARS-CoV-2 genomes from one region allows detailed epidemiology and enables local outbreak management

Abstract: The COVID-19 pandemic has spread rapidly throughout the world. In the UK, the initial peak was in April 2020; in the county of Norfolk (UK) and surrounding areas, which has a stable, low-density population, over 3,200 cases were reported between March and August 2020. As part of the activities of the national COVID-19 Genomics Consortium (COG-UK) we undertook whole genome sequencing of the SARS-CoV-2 genomes present in positive clinical samples from the Norfolk region. These samples were collected by four majo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…The presence of lineage A viruses from lethal and community cases throughout Uganda indicates that this lineage is circulating in Uganda and capable of producing a severe infection. Several variant lineages were observed at low frequencies and only briefly and may have undergone apparent extinction, similar to patterns observed in the UK (12) and Scotland (13).…”
Section: Main Textsupporting
confidence: 70%
See 1 more Smart Citation
“…The presence of lineage A viruses from lethal and community cases throughout Uganda indicates that this lineage is circulating in Uganda and capable of producing a severe infection. Several variant lineages were observed at low frequencies and only briefly and may have undergone apparent extinction, similar to patterns observed in the UK (12) and Scotland (13).…”
Section: Main Textsupporting
confidence: 70%
“…A number of A and B variant lineages were observed briefly at low frequencies and may have undergone extinction, similar to patterns observed in the UK (11) and Scotland (12). Genomes identified from a truck driver are often observed basal to community clusters (Figure 2), suggesting the importance of this route in the introduction and spread of the virus into Uganda.…”
Section: Main Textsupporting
confidence: 68%
“…2,3 Since the first full SARS-CoV-2 genome was published in January 2020 4 , sequencing of specimens from COVID-19 patients has allowed tracking of viral spread and identification of novel strains. [5][6][7][8][9][10][11] Seminal work early in the pandemic demonstrated how SARS-CoV-2 had entered Washington state in the US 2 , with most early infections linked to a single introduction in late January or early February. In Northern California, analysis of 36 early samples demonstrated that there were multiple points of entry.…”
Section: Introductionmentioning
confidence: 99%
“…A concentrated, ongoing, local approach to genomic surveillance is critical for the identification of variants and establishing epidemiological links with the trend of the outbreak 5,7,12,22 . This has also proved critical for local outbreak management and informed policy decisions across the world 5,7,37,38 .…”
Section: Introductionmentioning
confidence: 99%